The Discourse on the Difference Between Audacity and Real Fortitude in De bellis by Procopius of Caesarea - Michał Stachura (Classica Cracoviensia, 2024)
In De bellis by Procopius of Caesarea, there are multiple, though quite dispersed, instances of a discourse concentrated thematically on the distinction between true fortitude and audacity, with the latter being a mere semblance of the former, and actually a vice that is just the opposite of fortitude. The weight of this discourse comes from the role played by the virtue of fortitude in Procopius’ vision of history – being, on the one hand, the proper motive for preserving the remembrance of martial deeds and, on the other hand, the human-related factor that makes the greatest impact on the course of history. To understand this discourse properly, we need to abandon modern insights (with the mediaeval origin) expressed by concepts such as ‘courage’ and ‘bravery’ that blurred the boundary between virtue and emotion. Analysis of this discourse points to a relationship between real fortitude and prudence/integrity, while audacity is related to cowardice in the sense that it turns into the latter instantly in the face of danger (a stereotypical characteristic of villains in Antiquity). Likewise, seeking a certain death would be an act of audacity, not fortitude. However, a closer analysis of individual cases within this discourse shows a surprising rule: nearly all of them are examples of the moral philosophy applied in a perverse manner, to justify often disgraceful acts. Procopius himself, even though considering the reckless risking of one’s life as unworthy of fortitude, looks with admiration on all those who choose fighting until the end over accepting the shame of surrender (including also the opponents of Rome such as Vandals, Goths, and Persians). It appears then that the Late-Antique historiographer had already viewed the Platonic-Aristotelean distinction of fortitude and audacitywith some reserve, being closer in spirit to a new  conception of fortitude, later on to be expressed by the term ‘courage’.